Strivāda vimarśa musugulō viplavōdyamaṃpaī Kātyāyani-Jyōtirāṇila avakāśavāda dāḍini khaṇḍiñcaṇḍi śrāmika mahiḷā udyamānni balaparacaṇdi - Svarṇalata, M. (Pratulaku, Gōru Mādhavarāvu, 1999)
On revisionist tendencies in feminist criticism in the context of a debate on Marxism in Andhra Pradesh, India.